Working methodology with public universities in peru during the pandemic-continuity of virtual/online teaching and learning - Martín-Cuadrado, Ana María (2021)
This article describes the consultancy provided by the UTEC-UNED-TECSUP University Consortium to six national universities in Peru, during the COVID-19 state of emergency. This action aims to promote the techno-pedagogical change from a face-to-face to a virtual/online educational context. The process consists of three stages that ensured the continuity of the virtual/online educational service: diagnosis, design, and training, to strengthen instructional and digital competencies, support, and techno-pedagogical monitoring. It includes the basic principles of constructivist and constructionist learning theories for active and quality teaching and learning for the agents involved, and, in addition, the guidelines set by the emerging Peruvian regulations during the pandemic to move towards a digital university model according to the times. After a 157-day intervention, the analysis of the results raises some reflections: the importance of the socio-cultural context and its influence on the concept and development of the instructional act; the concept of distance learning in territories where connectivity is the main difficulty, and the university institution, in terms of a non-presential educational model with open and versatile methodologies, which anticipates a long process, involves a scheduled follow-up, requires fluid communication and demands continuous feedback.